2012
DOI: 10.1111/j.1600-0765.2012.01499.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of EMD in combination with bone swaging and calcium phosphate bone cement on periodontal regeneration in one‐wall intrabony defects in dogs

Abstract: These results indicate that treatment with EMD + BS + CPC promotes favorable periodontal healing in one-wall intrabony defects in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…[ 15 18 ] However, in the study, alveolar bone and cementum formation almost reached 64–79% of the height of defect and 33–41% bone area formation (not including the residual ABB granules) in the ABB + CM groups. Although the 1-wall intrabony defect size (7 mm × 4 mm) was found healing within an 8-week period in this study, which indicated greater challenge to spontaneous healing than the generally reported 1-wall intrabony defects (4 mm × 5 mm or 3 mm × 5 mm) within an 8- or 12-week,[ 19 20 ] ABB + CM group exhibited more bone regeneration (71.38% on average in height) than those reported only with grafts (36.5–60.0% in newly formed bone height)[ 19 21 22 ] and even than that using grafts combined with cells or growth factors (31–71% in newly formed bone height). [ 23 24 ] In addition, treatment with ABB + CM did not show less periodontal regeneration in 1-wall intrabony defects than that in the 3-wall intrabony defect within the limits of this study.…”
Section: Discussionmentioning
confidence: 56%
“…[ 15 18 ] However, in the study, alveolar bone and cementum formation almost reached 64–79% of the height of defect and 33–41% bone area formation (not including the residual ABB granules) in the ABB + CM groups. Although the 1-wall intrabony defect size (7 mm × 4 mm) was found healing within an 8-week period in this study, which indicated greater challenge to spontaneous healing than the generally reported 1-wall intrabony defects (4 mm × 5 mm or 3 mm × 5 mm) within an 8- or 12-week,[ 19 20 ] ABB + CM group exhibited more bone regeneration (71.38% on average in height) than those reported only with grafts (36.5–60.0% in newly formed bone height)[ 19 21 22 ] and even than that using grafts combined with cells or growth factors (31–71% in newly formed bone height). [ 23 24 ] In addition, treatment with ABB + CM did not show less periodontal regeneration in 1-wall intrabony defects than that in the 3-wall intrabony defect within the limits of this study.…”
Section: Discussionmentioning
confidence: 56%
“…However, Zetterstrom et al and Hagenaars et al reported no differences in pacients' perceptions and postsurgical healing between surgeries with EMD and flap operations [16][17][18]. Saito et al in a study regarding the treatment of periodontal defects with enamel matrix derivative, showed after three to six months that periodontal surgery with EMD results in a clinically relevant reduction in probing depth and a gain in clinical attachment [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…These defects were created with trephine burs size 4 under copious amounts of saline solution irrigation. The bone obtained with intrabone marrow penetration was used in treatment as the source of autogenous bone graft (10) . Experimental periodontitis associated with one wall osseous defect was induced on the premolars of each quadrant of both jaw (11).…”
Section: Surgical Proceduresmentioning
confidence: 99%